Det mystiske X. Rekonstruktionen af tabte identiteter - Bojlén, Benedicte (Tidsskriftet Antropologi, 2019)
The article describes the methodological development of Identification in forensic medicine, thereby sketching out the historical interconnection between art, medicine and anthropology. Social anthropology usually understands personal identity as a person’s sense of belonging to a certain group on various grounds. Physical anthropology, on the other hand, understands personal identity as identification. The reconstruction of a person’s identity from bodily remains can be done only with help of measurements and use of “scientific” systems for classification of humans. The article shows these systems as cultural constructs. Also artists are sometimes called in to help reconstruct a human face for identification. Like natural scientists, artists have systems of signs - only they seem to escape conscious classifications, putting science in a dilemma. The continued use of medical artists and computerised “phantom” images when constructing a hypothetical identity, urges the author to recommend further research into the semiotics of art and science, especially with the regard to culturally determined ways of seeing, measuring and classifying.